The Andean Community in face of the overlapping of regional integration processes - Loss de Araujo, Flavia; Araujo, André Leite [UNESP] (Taylor & Francis, 2024)
The 21st century has seen the intensification of new regional arrangements in Latin America, constituting a new phase for the Andean Community (CAN). There have been significant changes in the governments of members and the consequence divergence of perspectives on integration, which have pushed the countries of the Andean bloc to participate in other arrangements and caused Venezuela to leave the CAN. Faced with the changing dynamics of so-called overlapping, the CAN went through a crisis and adapted as survival strategies allowing its members to participate in other free trade mechanisms and extra-bloc arrangements. In this context, the current article aims to understand how overlapping has affected the Andean bloc’s trade flow. The exploratory analysis conducted here showed that dual membership had a limited impact on intra-regional flows. Trade within the bloc remained stable despite the change of members and their overlapping in other regional projects.
A Comunidade Andina frente ao overlapping de processos de integração regional
Keywords: Andean Community; free trade; international organizations; Latin America; overlapping; regionalism